ANALISIS PERILAKU KEAMANAN INFORMASI PENGGUNA APLIKASI SHOPEE MENGUNAKAN FRAMEWORK SECURITY BEHAVIOR INTENTIONS SCALE (SeBIS) - Yufentus Leokuna; Sintaria Sembiring (Djtechno: Jurnal Teknologi Informasi, 2026)
The rapid development of digital technology has increased the use of e-commerce platforms, making online transactions easier while also raising concerns regarding users’ information security. This study aims to analyze the level of information security behavior of Shopee users in Bandung City using the Security Behavior Intentions Scale (SeBIS) framework and examine the relationship between each dimension and users’ information security behavior. This research employed a quantitative survey approach using an online questionnaire covering four SeBIS dimensions: proactive awareness, password generation, software updating, and device securement. A total of 251 active Shopee users participated in this study, with the sample size determined using the Lemeshow formula with a 10% margin of error. Data analysis was conducted through validity testing, reliability testing, descriptive analysis, and Pearson correlation analysis using IBM SPSS Statistics. The results show that the information security behavior of Shopee users in Bandung is categorized as high. All SeBIS dimensions show positive and significant relationships (p < 0.001) with information security behavior with very strong correlations (r = 0.854–0.902), where device securement has the strongest relationship..